Pengaruh Umkm Usaha Mebel dan E-Commerce Terhadap Meningkatkan Pertumbuhan Ekonomi di Desa Krapyak Kota Pasuruan - Siti Istifadah; Sugeng Pradikto (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study is to analyse the impact of MSMEs on economic growth and e-commerce usage of furniture stores in Krapyak Village, Pasuruan City With the help of a quantitative approach, data was collected by distributing questionnaires to furniture entrepreneurs in the village through WhatsApp groups. The survey aimed to measure the impact of using e-commerce platforms on sales growth, market access, and job creation. The findings show that the use of e-commerce has a significant positive impact on sales volume growth. Sales volume that was previously limited to the domestic market can now reach a wider market both domestically and internationally. In addition, e-commerce will also help increase the number of workers in the furniture industry. However, obstacles that need to be overcome include the lack of skills in using digital platforms and the limited internet infrastructure that is not evenly distributed throughout the villages. In conclusion, the utilisation of e-commerce has opened up greater market opportunities, generated new jobs for Krapyak villagers and boosted the village's economic growth.